Cryoballoon ablation in obese patients: it is worth it, let us work it. (3rd October 2022) - Boehmer, A A; Rothe, M; Nussbaum, E; Dobre, B C; Kaess, B; Ehrlich, J R
Abstract: Background: Obesity is a major risk factor for atrial fibrillation (AF) development and of increasing prevalence in western countries. Safe and effective treatment methods for obese patients with AF are therefore important. Cryoballoon pulmonary vein isolation (CryoPVI) is a well-established therapy for symptomatic AF but data regarding obese patients are lacking. Objective: To prospectively compare efficacy, safety and periprocedural parameters of CPVI in normal-weight and obese (Body-Mass-Index (BMI) ≥30kg/m 2 ) patients. Methods: We analyzed consecutive patients who underwent CryoPVI in a single-center cohort between 2018 and 2020. CryoPVI was performed in a standardized fashion. Follow-up was performed at 3, 6, 12, 18 and 24 months after CryoPVI. Endpoints were: symptomatic AF relapse for efficacy and bleeding, phrenic nerve injury, stroke or death for safety. Periprocedureal parameters were observed. Results: We included 464 patients into the analysis, of these 331 patients had normal BMI (mean BMI 25.5±2.8 kg/m 2, age 70±10 years, CHA2DS2-VASc 2.7±1.5, 56% male) while 133 patients (28.7%) suffered from obesity (mean BMI 33.2 kg/m 2, age 67±9 years, CHA2DS2-VASc 2.7±1.4, 55% male). After 24 months freedom from AF relapse was similar for normal-weight and obese patients (58.8% vs. 61%, P=0.78, Figure 1A). Primary safety end point occurred in form of pericardial effusion or phrenic nerve injury in five patients with normal BMI (1.5%) and none obesity group. No deaths or strokes were observed in either group. Compared with control left-atrial dwell time (39.7±14.6 min vs. 44.8±18.7 min, P=0.002, fluoroscopy time (7.3±3.6 min vs. 8.3±4.1 min, P=0.013), contrast dye use (64.6±34.3 ml vs. 74.5±39.5 ml, P=0.009), and radiation dose (224.8±164.2 cGy·cm 2 vs. 533.3±655.6 cGy·cm 2, P<0.001) were significantly higher in obese patients (Figure 1B–E). Conclusion: CryoPVI is safe and effective in obese patients but achievement of PVI is associated with longer procedure times, higher radiation exposure and contrast dye use. Funding Acknowledgement: Type of funding sources: None.